The urban bioregion as form and project of the co-evolution between urban and rural domain. the case of the Florence metropolitan area - Fanfani, David (International Journal of Engineering and Technology, 2018)
Urbanization processes entailed, especially in western countries, growing interaction between urban and rural domain alongside with ‘resilience’ problems also related to global economic, climate and ‘transition’ matters. That calls for a ‘re-embedding’ of cities in their surrounding regions. In such a framework, this article explores the opportunity of recovering, in planning practices, the ‘urban bioregion’ concept, as key feature for balanced and co-evolutionary polycentric urban regions. That allows to point out, as in the case described relatively to Florence MA, the need to adopt integrated and bottom-up approach, in order to overcome routine and path-dependent practices in periurban areas planning.